Interprofessional Education (IPE) in a Pediatric Simulation: Case of an Infant with Fever - Mary Sanders; Daniel Richards; Ladan Panahi (Association of American Medical Colleges, 2013)
Abstract Introduction Interprofessional Education (IPE) occurs when members of different professions work together. In an increasingly multidisciplinary health care environment, health professions educational programs which incorporate IPE into the curriculum are preparing students to work as part of a healthcare team. In an effort to help students achieve greater collaboration skills, a clinical simulation was designed to be implemented into the students' pediatric experiential learning. This simulation allows students from Texas A&M University Health Science Center's Colleges of Medicine, Nursing, and Pharmacy to collaborate as they work through a common pediatric clinical scenario. Methods The simulation consists of stations in which collaborative practice is encouraged in the context of an infant presenting with fever. Students are grouped into interprofessional teams depending upon the ratio of nursing, medicine and pharmacy participants. Debrief is conducted with a focus on the Interprofessional Core Competencies. Results In 2012-2013, we successfully implemented the interprofessional simulation case with a total of 66 students. Learners were evaluated with a postexercise questionnaire containing a 5-point Likert scale, as well as short-answer questions. A total of 37 College of Nursing, 21 College of Medicine, and eight College of Pharmacy students completed the survey. Approximately 13% of the students did not understand the role of the other interdisciplinary team members prior to the simulation activity but 91% felt respect for the roles of other health professionals is an important component of patient care. Approximately 62% of the students reported they had not previously participated in an interprofessional education simulation activity before. The majority of the students felt comfortable sharing their input in patient care (91%) and felt they were able to communicate their responsibility in caring for the patient (99% agreed or strongly agreed). Preliminary qualitative data obtained from the postexercise questionnaire short answer portion suggests that students in each college recognize the benefits of communicating with members of other health care professions and understand the roles/responsibilities of other team members. When asked what students' felt was the most valuable aspect of the simulation, 32% stated the opportunity to understand the roles of other healthcare professionals and another 32% stated the ability to work in a team and collaborate with other healthcare professionals. Approximately 14% of students left comments asking for more interdisciplinary simulations in the future. The main comment and suggestion the students made regarding the least valuable aspect of the simulation were the opportunity to work in smaller groups in the selective stations before discussing the aspects of each station in a large group. Discussion In an increasingly multidisciplinary health care environment, health professions educational programs which incorporate IPE into the curriculum are preparing students to work as part of a healthcare team. This simulation allows medical, nursing, and pharmacy students to collaborate as they work through a common pediatric clinical scenario.